Keadilan Ekonomi dalam Perspektif Teologi Kristen: Mengkritisi Kebijakan Pemerintah Terkait Kelangkaan Minyak Goreng dan Gas - Purwonugroho, Daniel Pesah (Teokristi: Jurnal Teologi Kontekstual dan Pelayanan Kristiani, 2025)
This paper is written to criticize government policies related to scarcity of cooking oil and gas. The criticism is based on economic justice in the perspective of Christian theology. Christian theology provides a perspective on social justice perspective that favors the poor. Christian ethics also highlights the correct and responsible distribution of resources. With the practice of this, the distribution of cooking oil and gas should be enjoyed by the Indonesian people, especially the poor. Fair and responsible distribution is the key to achieving social justice. Through a descriptive qualitative approach descriptive qualitative approach, the author tries to unravel economic justice in a Christian perspective. Christian perspective. The description will be useful to provide criticism for government policies related to the scarcity of cooking oil and gas.